[123I]FP-CIT SPECT shows a pronounced decline of striatal dopamine transporter labelling in early and advanced Parkinson's disease. Issue 2 (February 1997) - Booij, J; Tissingh, G; Boer, G J; Speelman, J D; Stoof, J C; Janssen, A G; Wolters, E C; van Royen, E A
Abstract : OBJECTIVES: The main neuropathological feature in Parkinson's disease is a severe degeneration of the dopaminergic neurons in the substantia nigra resulting in a loss of dopamine (DA) transporters in the striatum. [123I]beta-CIT single photon emission computed tomography (SPECT) studies have demonstrated this loss of striatal DA transporter content in Parkinson's disease in vivo. However, studies with this radioligand also showed that an adequate imaging of the striatal DA transporter content could only be performed on the day after the injection of radioligand, which is not convenient for outpatient evaluations. Recently, a new radioligand [123I]FP-CIT, with faster kinetics than beta-CIT, became available for imaging of the DA transporter with SPECT, and the applicability of this ligand was tested in patients with early and advanced Parkinson's disease, using a one day protocol. METHODS: [123I]FP-CIT SPECT was performed in six patients with early and 12 patients with advanced Parkinson's disease, and in six age matched healthy volunteers. RESULTS: Compared with an age matched control group striatal [123I]FP-CIT uptake in patients with Parkinson's disease was decreased, and this result was measurable three hours after injection of the radioligand. In the Parkinson's disease group the uptake in the putamen was reduced more than in the caudate nucleus. The contralateral striatal uptake of [123I]FP-CIT was significantly lower than the ipsilateral striatal uptake in the Parkinson's disease group. Specific to non-specific striatal uptake ratios correlated with the Hoehn and Yahr stage. A subgroup of patients with early Parkinson's disease also showed significantly lower uptake in the putamen and lower putamen:caudate ratios than controls. CONCLUSION: [123I]FP-CIT SPECT allows a significant discrimination between patients with Parkinson's disease and age matched controls with a one day protocol, which will be to great advantage in outpatient evaluations.